2022
DOI: 10.3205/hta000133
|View full text |Cite
|
Sign up to set email alerts
|

Disposal practices for unused and expired medications: pilot data from three cities in three countries

Abstract: Objective: To collect pilot data on medication disposal practices of unused and expired medications from three cities in three countries. Methods: A cross-sectional survey was conducted in Pittsburgh, United States (US); Turin, Italy; and Kobe, Japan. A convenience sampling was utilized through drug take-back programs in Pittsburgh, US; pharmacy customers in Turin, Italy; and pharmacy students and family members in Kobe, Japan. Descriptive analysis was conducted to assess med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This could be due to various barriers like lack of access to drug takeback programs and inconvenience, as identified in this study. Previous studies have also identified similar barriers and emphasized the need for policies to make drug take-back programs more accessible and convenient [31][32][33].…”
Section: Discussionmentioning
confidence: 88%
“…This could be due to various barriers like lack of access to drug takeback programs and inconvenience, as identified in this study. Previous studies have also identified similar barriers and emphasized the need for policies to make drug take-back programs more accessible and convenient [31][32][33].…”
Section: Discussionmentioning
confidence: 88%
“…In order to obtain data from the first sample group of the study, a questionnaire was developed based on the questions of previous studies [ 11 14 ]. The content of this form includes socio-demographics, practices about on unused medicines, disposal practices, number of unused medicines and generic names of medicines.…”
Section: Methodsmentioning
confidence: 99%